Implementation of SIPOC analysis as productivity improvement in tilapia aquaculture - Indah Apriliana Sari Wulandari; Shazana Dhiya Ayuni; Lukman Hudi (Universitas Muhammadiyah Magelang, 2023)
Tilapia aquaculture in tarpaulin ponds is a new business pursued by residents of Kramatjegu Village, East Java, since the Covid-19 pandemic hit Indonesia. Restrictions on social activities, forcing residents to learn fish farming in a self-taught way. However, the problem that arose in the first month of cultivation was that many tilapia died and by the third month all the tilapia were gone. Lack of knowledge about fish farming techniques, lack of correction of water and feed quality, and inaccurate handling of fish problems are problems that need to be resolved. The purpose of this community service is to conduct counseling related to fish farming techniques, as well as giving work instructions (IK) to residents. While the method applied to this activity is counseling, as well as an introduction to the concept of Supplier-Input-Process-Output-Customer (SIPOC). The result of this counseling is an increase in residents' knowledge about preparation for making tarpaulin ponds, seed selection and production, feeding techniques, harvesting, and selling fish.